Measuring students’ writing skills using Facebook group application in EFL context - Geminastiti Sakkir; Syarifuddin Dollah (International Journal of Humanities and Innovation (IJHI), 2019)
This research aims to measure the effectiveness of students’ writing skill through the application of Facebook group in English learning. It employed a quantitative method using the pre-experimental design. The subject of the research was the second-semester students of one of the private universities in South Sulawesi, Indonesia in the academic year of 2017/2018. They were selected purposively due to the writing problems occurred in the class. The total number of the sample was 20 students, which were taken by census sampling technique. The instrument was a writing test to obtain data on the students’ writing achievement through the Facebook group. The data analysis found that the students’ mean score in English writing was significantly improved. The students’ mean score in the pretest was 65.30 while their mean score in the posttest was 78.05. The t-table was also lower than the t-test, that is 2.093<6.04. Based on the result the researchers concluded that the application of Facebook group in English learning improved students’ ability in writing.